LEGAL STUDY ON RATE INCREASE POLICY FOR HEALTH BPJS PARTICIPANTS DURING THE COVID-19 PANDEMIC - Dhiya Haniyah Br Manurung; Wessy Trisna; Beby Suryani Fitri (Universitas Medan Area, 2022)
The purpose of this study is how to regulate the legal regulation of the tariff increase policy for BPJS participants during the covid-19 pandemic and what is the mechanism/procedure for submitting the rights of BPJS participants after the increase in BPJS Health rates during the covid-19 pandemic. The type of research used in writing this thesis is normative juridical which is descriptive analysis. The approach method used in this research is the statutory approach. The results of the study, the legal regulation of the tariff increase policy for BPJS participants during the covid-19 pandemic is regulated in Presidential Regulation Number 64 of 2020 concerning the Second Amendment to Presidential Regulation Number 82 of 2018 concerning Health Insurance. The increase in BPJS contributions during the Covid-19 pandemic was inappropriate, because it was not in accordance with the mandate of the 1945 Constitution as the basis of the Republic of Indonesia, namely Article 28 H (1) and paragraph (3). The impact of the policy of increasing BPJS rates during the Covid 19 pandemic includes positive and negative impacts, positive impacts, namely: increasing health services, covering the deficit, growth in the pharmaceutical sector, increasing hospital facilities and infrastructure, increasing socialization of the BPJS program, increasing the range of diseases borne. wide range of hospitals, while the negative impacts are: a decrease in the class of BPJS participants, the number of participants in the third grade, many people decide to stop paying contributions, a decrease in public interest, the shift of people to private insurance, inflation, increasing poverty.